The Role of Written Presentations in Teaching and Learning Languages - Shoxidova Mashxura Kobuljonovna (International Journal on Integrated Education, 2022)
This article provides advice on how to write a presentation. It discusses the initial writing, and then also explains how to review and edit your work. This will help to ensure that your presentation is as effective as possible. Witten presentations are an interactive form of learning activity, during which the speaker reports on the results of his project work, introduces students to new factual information, and the students listening to him learn new foreign language vocabulary, enrich their knowledge in the specialty.